2010
DOI: 10.1029/2009jc005922
|View full text |Cite
|
Sign up to set email alerts
|

Wyrtki Jet dynamics: Seasonal variability

Abstract: [1] This study examines the dynamics of the Wyrtki jets, which are strong equatorial zonal flows that occur typically during boreal spring and fall in the Indian Ocean. Our diagnosis relies primarily on a continuously stratified linear longwave ocean model driven by QuikSCAT zonal winds. Model results, which compare well with satellite altimetry and in situ current observations, indicate that the zonal currents propagate westward along the equator at semiannual periods with an average speed of −1.5 m s −1 . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
102
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 57 publications
14
102
0
1
Order By: Relevance
“…They were explained as a wind-driven response to zonal winds by O'Brien and Hurlburt (1974), who applied the theory of Yoshida (1959). The WJs have been observed to appear in the spring and the fall of every year on a regular basis (e.g., Nagura and McPhaden 2010;Nyadjro and McPhaden 2014), although the spring jets have been found to be weak in 2006 through 2009 (Joseph et al 2012). The strong response of the WJ to semi-annual forcing has been explained by resonant basin modes (Jensen 1993;Han et al 1999) based on the theoretical work of Cane and Moore (1981).…”
Section: Introductionmentioning
confidence: 99%
“…They were explained as a wind-driven response to zonal winds by O'Brien and Hurlburt (1974), who applied the theory of Yoshida (1959). The WJs have been observed to appear in the spring and the fall of every year on a regular basis (e.g., Nagura and McPhaden 2010;Nyadjro and McPhaden 2014), although the spring jets have been found to be weak in 2006 through 2009 (Joseph et al 2012). The strong response of the WJ to semi-annual forcing has been explained by resonant basin modes (Jensen 1993;Han et al 1999) based on the theoretical work of Cane and Moore (1981).…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al [2009] reported the westward phase propagation in the equatorial currents, which they attributed to the westward phase propagation of zonal winds in the western equatorial Indian Ocean. Nagura and McPhaden [2010a] studied this westward propagation in detail using a linear continuous stratified model, and interpreted the westward propagation as a result of a superposition of Rossby waves on a wind forced jet.…”
Section: Introductionmentioning
confidence: 99%
“…8a-c). In particular, a prominent signature of the Wyrtki Jet is evident in the subsurface Indian Ocean, which corresponds to strong equatorial zonal flows that occur typically during boreal spring and fall at semiannual periods with an average speed of −1.5 m/s (Nagura and McPhaden 2010). Further downward, the phase pattern basically exhibits a random nature, except for the SPCZ where a coherent feature can be marginally detected between ~100-300 m (Fig.…”
Section: Annual and Semiannual Phasesmentioning
confidence: 82%